2021
DOI: 10.3389/fimmu.2021.768435
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular CIRP-Impaired Rab26 Restrains EPOR-Mediated Macrophage Polarization in Acute Lung Injury

Abstract: Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a condition with an imbalanced inflammatory response and delayed resolution of inflammation. Macrophage polarization plays an important role in inflammation and resolution. However, the mechanism of macrophage polarization in ALI/ARDS is not fully understood. We found that mice with lipopolysaccharide administration developed lung injury with the accumulation of extracellular cold-inducible RNA-binding protein (eCIRP) in the lungs. eCIRP, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Lately, a study ( 74 ) has revealed the possible regulation pathway of eCIRP in ALI. It was found that the expression of CIRP increased in lung tissues of the LPS-induced ALI/ARDS mice and inhibited the polarization of M2 macrophages and increased the inflammatory response.…”
Section: Role Of Ecirp In Inflammatory Diseasesmentioning
confidence: 99%
“…Lately, a study ( 74 ) has revealed the possible regulation pathway of eCIRP in ALI. It was found that the expression of CIRP increased in lung tissues of the LPS-induced ALI/ARDS mice and inhibited the polarization of M2 macrophages and increased the inflammatory response.…”
Section: Role Of Ecirp In Inflammatory Diseasesmentioning
confidence: 99%
“…In this study, we aimed to identify a novel therapeutic approach that can effectively impede the progression of frostbite and expedite recovery with minimal adverse effects. MD2 has been considered as a therapeutic target for various mouse disease models, including acute lung injury, 24 stroke, 17 perioperative neurocognitive disorder, 25 and sepsis 18 , 26 mice models. Besides, CIRP-related peptide has demonstrated effective anti-DAMP damage effects in stroke and sepsis mouse models with low confirmed side effects.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Macrophage erythropoietin receptor signaling is impaired by eCIRP through Rab26 during acute lung injury/acute respiratory distress syndrome, leading to restrained M2 macrophage polarization and delayed resolution of inflammation. 20 Furthermore, eCIRP dysregulates macrophage bacterial phagocytosis during sepsis. 21 Intravenous injection of recombinant murine CIRP in C57BL/6 mice causes lung injury, as evidenced by vascular leakage, edema, increased leukocyte infiltration, and cytokine production in the lung tissue, accompanied by endothelial cell activation and pyroptosis in isolated primary mouse lung vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%